Efektivitas Model Problem Based Learning Berbantuan Media Digital untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMA pada Materi Pemanasan Global - Nyai Ratu Syahira; Lina Aviyanti; Dedi Sasmita (Mataram University, 2026)
Problem-solving ability is one of the essential 21st-century competencies that students must develop. However, a preliminary study conducted at a public senior high school revealed that students' problem-solving ability remained low, with an average score of 42.32, far below the minimum mastery criterion (78), due to teacher-centered learning practices. This study aimed to analyze the improvement and effectiveness of the Problem Based Learning (PBL) model assisted by the IMOGLOW Flipbook E-Module digital media in enhancing students' problem-solving ability on the topic of Global Warming, as well as to examine students' responses to its implementation. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The participants consisted of 60 tenth-grade science students (30 students in the experimental class and 30 students in the control class), selected through convenience sampling. Data were collected using pretests, posttests, and a Likert-scale response questionnaire. The data were analyzed using the N-Gain test, prerequisite tests (Shapiro-Wilk and Levene's tests), the Mann-Whitney U test, and Cohen's d effect size with IBM SPSS Statistics version 26. The results indicated that the experimental class achieved a higher average N-Gain score (61.78%, moderately effective) than the control class (42.99%, less effective), with an Asymp. Sig. (2-tailed) value of < 0.001 and a Cohen's d effect size of 1.272, indicating a very large effect. In addition, students showed highly positive responses toward the learning implementation (89.17%, very good). The study concludes that integrating the Problem Based Learning model with the interactive IMOGLOW Flipbook E-Module is effective in improving students' problem-solving ability on the topic of Global Warming.